2003
DOI: 10.1021/jp027066w
|View full text |Cite
|
Sign up to set email alerts
|

Significance of Charge Regulation in the Analysis of Protein Charge Ladders

Abstract: Analysis of protein charge ladders using capillary electrophoresis (CE) provides a method of determining charges of proteins. This method has disregarded the effect of charge compensationsa response of the protein and its environment to a change in electrostatic potential on the surface of the protein. This work examines the difference in charge, ∆Z, between the first two rungs of the ladder of bovine carbonic anhydrase II (BCAII) as a function of pH and ionic strength using CE. These data were analyzed in thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
83
0
8

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 37 publications
(93 citation statements)
references
References 26 publications
(56 reference statements)
2
83
0
8
Order By: Relevance
“…The Lee model, described in section II.C, predicts a value of ∆Z EM 47 The accuracy in values of ∆Z EM reflects the accuracy with which electrostatic models predict values of pK a . The accuracy in values of ∆Z BE reflects the accuracy of the experiments and of the mobilities predicted by the BE model.…”
Section: Resultsmentioning
confidence: 99%
“…The Lee model, described in section II.C, predicts a value of ∆Z EM 47 The accuracy in values of ∆Z EM reflects the accuracy with which electrostatic models predict values of pK a . The accuracy in values of ∆Z BE reflects the accuracy of the experiments and of the mobilities predicted by the BE model.…”
Section: Resultsmentioning
confidence: 99%
“…The increased participation of charged residues in the crystal contacts of [CA-(NHCOCH 3 Aly-perhaps as a result of its charge neutrality, increased surface area, and/or ambidexterity in hydrogen bonding-can more easily accommodate a range of binding partners in crystal contacts.…”
Section: Contact Regions Accommodate Charged Residues Through Salt Brmentioning
confidence: 99%
“…We used acetic anhydride to acetylate the lysine residues of CA (this procedure is quantitative; see Supporting Information); we refer to crystals of the peracetylated variant as [CA-(NHCOCH 3 ) 18 ] -19 . Capillary electrophoresis confirmed that all 18 residues were acetylated (Figure S1) 16 ; X-ray crystallography allowed us to determine its structure, and, thus, permitted a comparison with the structure of wild-type CA, 6 which we, hereafter, refer to as [CA-(NH 3 + ) 18 ] -3.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus eliminating the positive charge from ε-NH+ group and replacing with negative charge would increase the net negative charge by 2 units. However this change would be less than 2 units due to charge regulation, due to the adjustment of protonation states of other ionizable residues predominantly histidine in a manner that reduces the total change in charge [18,21].…”
mentioning
confidence: 99%